Eficiência das unidades judiciárias de entrância inicial: uma análise empírica para o Tribunal de Justiça do Estado do Ceará, no período de 2017 a 2019 - Lima, George Dienne Amaro de (2021)
The present work analyzed the efficiency of the units of initial jurisdiction of the court of justice of the state of Ceará (TJCE), from July 2017 to December 2019. To create an efficiency rank for these units, a base was built of data, containing the variables, new cases, pending cases, cases downloaded, a total number of permanent employees, without a contract, assigned, outsourced and interns from 99 units investigated. The sources used were the justice in numbers report of the national council of Justice (CNJ) and the productivity report of the judges of the general internal affairs of justice of the TJCE. The analysis took place through an econometric model of Data Envelopment Analysis (DEA) oriented to outputs. The resulting model, it is concluded that the most efficient judicial units, in the analyzed period, were Santana do Acaraú, Ibiapina, Pentecoste, Caridade, Catarina, Piquet Carneiro, Ipueiras, Trairi, Milagres and Barro; the least efficient were Antonina do Norte, São Luís do Curu, Ibicuitinga, Porteiras, Fortim, Santana do Cariri, Acaraú, Itaitinga, Irauçuba and Jaguaruana.